A young adolescent with misdiagnosed attention deficit hyperactivity disorder: a case report - Pasquali, Marco A. B.; Parikh, Parinda; Onikura, Satomi (International Journal Of Community Medicine And Public Health, 2025)
Attention deficit hyperactivity disorder (ADHD) is a prevalent neurodevelopmental disorder, found in 5-7% of the general population globally, and characterized by inattention, hyperactivity, and impulsivity. The etiology of ADHD involves genetic susceptibility and environmental factors. ADHD has major influences on academic, occupational, and social performance. Diagnosis is based on DSM-5 or ICD-11 criteria, supplemented by clinical assessment and teacher and family rating scales. Treatment includes stimulant pharmacotherapies, such as methylphenidate (MPH) and amphetamines, and nonstimulant medications, such as atomoxetine, supplemented by psychosocial therapies, particularly in children. Appropriate diagnosis and treatment are necessary to prevent adverse consequences, which include educational impairment, work impairment, and comorbid psychiatric illnesses. This case report discusses a 16-year-old male patient with previous symptoms of inability to focus on tasks and follow instructions correctly, leaving schoolwork incomplete, catatonia, psychotic behavior, and more. The patient was misdiagnosed with a psychotic disorder and received a series of pharmacological treatments and even electroconvulsive therapy without an appropriate clinical response. After ADHD was diagnosed and managed appropriately, the patient responded favorably to the procedures he underwent. The case highlights the extreme importance of thorough psychiatric evaluations, particularly the mental state examination (MSE), to facilitate accurate diagnoses and personalized treatment plans. In addition, a discussion was held on the symptoms of inadequately treated ADHD and why it occurs based on neuroimaging studies.